Rx to Lead-Examining Pharm.D. Leadership Development Commencing during Pharmacy School through Co-Curricular Engagement - Matthew J. Smith; Jason K. Wallace (MDPI AG, 2024)
Leadership development in college is frequently cited as developing during undergraduate years. Nevertheless, some graduate and professional students develop further as leaders through involvement at the graduate level. This paper explores a case study examining the ways Doctor of Pharmacy (Pharm.D.) students commenced leadership development during pharmacy school through their co-curricular involvement.